Case Report: Splanchnic Vein Thrombosis as a Complication of Necrotizing Acute Pancreatitis in a Pediatric Patient - Figueroa-Sánchez, Mauricio; Nuño-Guzmán, Carlos M.; Álvarez-López, M. Carmen; Ordónez-Cárdenas, Mariana; Montaño-Rodríguez, Leidy J. (Frontiers in Surgery, 2022)
Splanchnic vein thrombosis is an unusual manifestation of venous thromboembolism and includes portal vein thrombosis, mesenteric veins thrombosis, splenic vein thrombosis, and the Budd-Chiari syndrome. The most common risk factors include hematologic and autoimmune disorders, hormonal therapy, liver cirrhosis, solid abdominal cancer, recent abdominal surgery, and abdominal infections or inflammatory conditions, such as pancreatitis. Splanchnic vein thrombosis in acute pancreatitis is most commonly associated with the severe form of the disease and pancreatic necrosis. This report describes a case of splanchnic vein thrombosis as a complication of necrotizing acute pancreatitis in a pediatric patient. Splanchnic vein thrombosis was incidentally detected on contrast-enhanced computed tomography to assess the pancreas. There was no evidence of prior risk factors for the thrombotic condition. The patient was treated with anticoagulation and showed complete resolution after recovery from necrotizing acute pancreatitis, at a 16-month follow-up. The complication of necrotizing acute pancreatitis with splanchnic vein thrombosis in pediatric age is a rare presentation.